Analysis of Supply Chain Commodity Rajungan (Portunus pelagicus) in Ujungpangkah District Gresik Regency of East Java - Bakhrul Ilmi; Harsuko Riniwati (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
Rajungan (Portunus pelagicus) is sea crab which found on Indonesia waters. Rajungan also kind of fisheries comodity which have important economic value and high enough in Indonesia. This research doing for knowing supply chain of Rajungan from upstream to downstream at Pangkah Wetan Village’s Ujungpangkah District, Gresik. Method of research used descriptive with qualitative approach. Number of sample used amount 50 respondents therefore can be said sampling is full. Method of collected data using interview, observe, documentation, and literature review. Method of data analysis used describtive qualitative and enhanced with triangulasi. Result of analysis supply chain research rajungan comodities produced by researchers are there supplu chain’s flow where the difference is when fishermans borrow to their boss and fisherman who determining to own money. The member who run activitiy is fisherman, the large scale traders, the large scale traders large and companies. Market share of rajungan is great demand in international market likes United State of America, Singapore, China, Japan, and others. The trust among partners and making fisherman-company’s contract deals is urgenly needed for advantages to both sides.